Patient preferences in allergy immunotherapy (AIT) in Germany: A discrete-choice-experiment - Kathrin Damm; Janina Volk; Andreas Horn; Jean-Pierre Allam; Ninette Troensegaard-Petersen; Niels Serup-Hansen; Thomas Winkler; Ivonne Thiessen; Kathrin Borchert; Eike G. Wüstenberg; Thomas Mittendorf (Health Economics Review, 2016)
Background: Allergic Rhinitis (AR) is a common disorder in Europe with Allergic Asthma (AA) as a frequent comorbidity. Allergy immunotherapy (AIT) is the only causal therapy of AR and AA, and can be administered as subcutaneous injections at the physician or as sublingual drops or tablets at home. The usual treatment duration is 3 years. Objective: This study aimed to elicit patient preferences to identify the AIT administration mode preferred by patients. Methods: A discrete-choice-experiment (DCE) was developed to determine how people weight different treatment options using a paper-based questionnaire from June to September 2014, including 16 study centres. Main inclusion criteria: >18 years, grass, birch and/or house dust mite AR with moderate to severe symptoms, AIT-naïve and AIT-indicated. DCE-attributes were: Administration form, number and duration of physician visits, frequency of life-threatening anaphylactic shocks, local side-effects and co-payments. Results: Two-hundred thirty-nine subjects participated, resulting in analysable 1842 choices. All attributes were significant predictors for the treatment-choice. Ranked by importance, the following first three attributes are most preferred by patients: - 1st Number and duration of physician visits: Fewer visits with shorter duration preferred (0.658*) - 2nd Frequency of life-threatening anaphylactic shocks: Lower risk of shocks preferred (0.285*) - 3rd Local side-effects: Preference for rash/swelling on upper arm over itching/swelling under the tongue (0.210*) (*coefficient-size represents relative importance of the attributes) Conclusion: The most important attribute is the number and duration of visits to a physician. A lower risk of life-threatening anaphylactic shocks was ranked as the second whereas co-payments and administration form play a limited role.
Keywords: 330; Allergic rhinitis; Allergy immunotherapy; Discrete-choice-experiment; Patient preferences; Sublingual immunotherapy-tablet